2017
DOI: 10.1128/genomea.00553-17
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequences of Six Enterococcus faecalis Strains Isolated from Malaysian Clinical and Environmental Origins

Abstract: Enterococcus faecalis is known to cause a variety of nosocomial infections, including urinary tract infections. Antibiotic resistance and virulence properties in this species are of public concern. The draft genome sequences of six E. faecalis strains isolated from clinical and environmental sources in Malaysia are presented here.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The frequency of Van genes in this study was much lower than the results obtained by two other studies (0.1% and 2.9%) in Peninsular Malaysia (Ibrahim et al, 2011;Mohamed et al, 2015). However, Weng et al (2013) and Daniel et al (2017) reported no VRE isolates in their Malaysian clinical isolates. Worldwide, the prevalence of antibiotic-resistant enterococcal infections is rising (Daniel et al, 2017;Shiadeh et al, 2019).…”
Section: Van Gene Frequencies and Multidrug Resistant Phenotypementioning
confidence: 98%
See 1 more Smart Citation
“…The frequency of Van genes in this study was much lower than the results obtained by two other studies (0.1% and 2.9%) in Peninsular Malaysia (Ibrahim et al, 2011;Mohamed et al, 2015). However, Weng et al (2013) and Daniel et al (2017) reported no VRE isolates in their Malaysian clinical isolates. Worldwide, the prevalence of antibiotic-resistant enterococcal infections is rising (Daniel et al, 2017;Shiadeh et al, 2019).…”
Section: Van Gene Frequencies and Multidrug Resistant Phenotypementioning
confidence: 98%
“…However, Weng et al (2013) and Daniel et al (2017) reported no VRE isolates in their Malaysian clinical isolates. Worldwide, the prevalence of antibiotic-resistant enterococcal infections is rising (Daniel et al, 2017;Shiadeh et al, 2019). Several studies reported that the VanA genotype was of serious concern due to the risk of transmission to other organisms and it was more common than VanB (Azzam et al, 2023).…”
Section: Van Gene Frequencies and Multidrug Resistant Phenotypementioning
confidence: 98%